2011
DOI: 10.1590/s1413-78522011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da perda sanguínea na artroplastia total do joelho com e sem soltura do torniquete

Abstract: Objective: To evaluate blood loss in patients submitted to cemented total knee arthroplasty with and without perioperative tourniquet release for hemostasis. Methods: Seventy-two patients (eighty knees) were submitted to total knee arthroplasty, allocated into two groups: in Group 1, in which the pneumatic tourniquet was maintained until suture and dressing of the operated wound, and Group 2, in which the pneumatic tourniquet was released intraoperatively after cementing the prosthesis, with direct hemostasis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“… 12 The moment of tourniquet removal as the best option for preserving blood stock, however, is controversial. Vasconcelos 4 observed that the removal of the intraoperative or postoperative tourniquet showed no difference in blood loss when comparing hemoglobin and hematocrit variation in the pre and postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 The moment of tourniquet removal as the best option for preserving blood stock, however, is controversial. Vasconcelos 4 observed that the removal of the intraoperative or postoperative tourniquet showed no difference in blood loss when comparing hemoglobin and hematocrit variation in the pre and postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“… 3 To reduce the number of blood transfusions in TKA, some care has been described to minimize perioperative and postoperative bleeding, such as occlusion of the femoral milling hole with bone graft, use of pneumatic tourniquet and suction drain, improvement of surgical technique, use of tranexamic acid, local infusion with norepinephrine and, more recently, the placement of gel with platelets in the operative wound. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain methods assist in reducing the bleeding, such as use of pneumatic cuffs, minimally invasive surgery and antifibrinolytic substances 1, 2, 3. With the aim of diminishing the number of blood transfusions during TKA, certain precautions for minimizing trans and postoperative bleeding have been described, such as use of pneumatic tourniquets and suction drains, improvement of surgical techniques, use of tranexamic acid, local infusion of norepinephrine, occlusion of the femoral milling orifice using a bone graft femoral, and most recently, placement of gel containing platelets in the operative wound 4 . Ischemia in TKA provides a cleaner surgical field, makes it easier to place the implants and provides a better interface for the cement 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…Для минимизации потери крови в интра-и послеоперационном периоде был предложен ряд методик, таких как окклюзия отверстия бедренной кости костным трансплантатом, использование пневматического жгута, усовершенствование операционного доступа, инъекции транексамовой кислоты в область сустава, местная инфузия адреналина, размещение геля с тромбоцитами в операционной ране и др. [4,5]. Однако у пациентов, перенесших операцию эндопротезирования, все же сохраняется относительно высокий риск возникновения массивного кровотечения в послеоперационном периоде [6].…”
unclassified